2006
DOI: 10.1093/nar/gkl403
|View full text |Cite
|
Sign up to set email alerts
|

RPA and PCNA suppress formation of large deletion errors by yeast DNA polymerase δ

Abstract: In fulfilling its biosynthetic roles in nuclear replication and in several types of repair, DNA polymerase δ (pol δ) is assisted by replication protein A (RPA), the single-stranded DNA-binding protein complex, and by the processivity clamp proliferating cell nuclear antigen (PCNA). Here we report the effects of these accessory proteins on the fidelity of DNA synthesis in vitro by yeast pol δ. We show that when RPA and PCNA are included in reactions containing pol δ, rates for single base errors are similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 40 publications
7
62
1
Order By: Relevance
“…The S-phase dNTP concentrations were calculated using measurements of dNTP levels in wild-type and pol3-R696W haploids containing pPOL3, as described in Table 3. Similar to other studies (8,44), the frequency of mutations resulting from synthesis by wild-type Polδ was not significantly different from the background mutation frequency for unfilled M13mp2 gapped substrate, regardless of whether the S-phase or standard 100 μM dNTP concentration was used (Table 2). In contrast, DNA synthesis by Polδ-R696W was highly error-prone.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The S-phase dNTP concentrations were calculated using measurements of dNTP levels in wild-type and pol3-R696W haploids containing pPOL3, as described in Table 3. Similar to other studies (8,44), the frequency of mutations resulting from synthesis by wild-type Polδ was not significantly different from the background mutation frequency for unfilled M13mp2 gapped substrate, regardless of whether the S-phase or standard 100 μM dNTP concentration was used (Table 2). In contrast, DNA synthesis by Polδ-R696W was highly error-prone.…”
Section: Resultssupporting
confidence: 85%
“…Yeast 2μ-based plasmids expressing POL3 from the GAL1 promoter, pBL336 (83), pBL335, and pBL335-5DV (44), which are referred to as pPOL3, pPOL3.GST, and pPOL3.GST-5DV in this study, were provided by Peter Burgers (Washington University School of Medicine, St. Louis, MO). Plasmids pPOL3.GST-R696W and pPOL3.GST-5DV,R696W were constructed by gap repair in yeast strains, in which the effects of these plasmids were studied.…”
Section: Methodsmentioning
confidence: 99%
“…34) was used for overproduction and purification of GSTtagged Rev1 fragments. Strains used in the UV sensitivity assays are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…These observations demonstrate that UL42 plays an important role in DNA replication fidelity. Although PCNA has been linked to replication fidelity in yeast, PCNA and gp45 have been linked to DNA replication fidelity in vitro (2,3,5,7,8,24), and UL42 can increase fidelity in vitro (4), to our knowledge, this is the first study to demonstrate an effect of a processivity factor in the replication fidelity of a virus in mammalian cells.…”
Section: Discussionmentioning
confidence: 98%
“…Mutations affecting PCNA can lead to elevated mutation rates in Saccharomyces cerevisiae (5,7). In vitro studies have demonstrated that the addition of PCNA can increase misincorporation errors by mammalian Pol ␦ on defined primer/templates (24) and reduce the rate of deletion mutations during the synthesis of repeated sequences by yeast Pol ␦ (8). T4 gp45 also can influence replication fidelity in vitro (2,3).…”
mentioning
confidence: 99%